Optical properties and structural phase transitions of W-doped VO2(R) under pressure. Issue 50 (21st June 2017) - Zhang, Huafang; Guan, Zhou; Cheng, Benyuan; Li, Quanjun; Liu, Ran; Zhang, Jing; Liu, Zhenxian; Yang, Ke; Cui, Tian; Liu, Bingbing
Abstract : The structure transition sequence of W–VO2 (R) nanoparticles follows rutile (R) → orthorhombic (CaCl2 -type) → monoclinic (Mx) within metallic phases. Abstract : We investigated the optical properties and structural phase transitions of W-doped VO2 (R) nanoparticles under pressure based on in situ synchrotron X-ray diffraction (XRD) and infrared (IR) spectroscopy. The structural transition sequence follows VO2 (R)–VO2 (CaCl2 -type)–VO2 (Mx) and VO2 (Mx)–VO2 (Mx′) within metallic phases, in compression and decompression processes, respectively, demonstrating that the structural transition can be decoupled from the metal-insulator transition (MIT). VO2 (R) and VO2 (CaCl2 -type) exhibit expected behavior of increased metallicity under pressure; surprisingly, VO2 (Mx) shows gradually decreased metallicity with increasing pressure and VO2 (Mx′) is still metallic under ambient conditions. We find that the reduced metallicity of VO2 (Mx) is attributed to W-doping induced local structure distortion in the high-pressure region, while the metallic properties of VO2 (Mx′) are associated with the enhancement of electron concentration due to the presence of W donors, which shifted the Fermi level toward the conduction band. The present results demonstrate that the structural transition is not the key factor in driving the metal-insulator transition, and provide an effective method for inducing MIT in VO2 (Mx′).